The Use of Research Methods in Psychological Research: A Systematised Review - Scholtz, Salomé Elizabeth; de Klerk, Werner; de Beer, Leon T. (Frontiers in Research Metrics and Analytics, 2020)
Research methods play an imperative role in research quality as well as educating young researchers however the application thereof is unclear which can be detrimental to the field of psychology. Therefore, this systematised review aimed to determine what research methods are being used, how these methods are being used and for what topics in the field. Our review of 999 articles from five journals over a period of five years indicated that psychology research is conducted in ten topics via predominantly quantitative research methods. Of these ten topics, social psychology was the most popular. The remainder of the conducted methodology is described. It was also found that articles lacked rigour and transparency in the used methodology which has implications for replicability. In conclusion this article, provides an overview of all reported methodologies used in a sample of psychology journals. It highlights the popularity and application of methods and designs throughout the article sample as well as an unexpected lack of rigour with regard to most aspects of methodology. Possible sample bias should be considered when interpreting the results of this study. It is recommended that future research should utilise the results of this study to determine the possible impact on the field of psychology as a science and to further investigation into the use of research methods. Results should prompt the following future research into: a lack or rigour and its implication on replication, the use of certain methods above others, publication bias and choice of sampling method.